Development and Mechanical Characterization of Al6061-Zircon Composites - Raju.T, Hemanth; S.Ramamurthy, V (International Journal of Engineering and Technology, 2018)
Composite materials are widely used in variety of applications such as aerospace, automotive and structural components resulting in savings of material and energy. Particulate reinforced Aluminium metal matrix composite materials which are having desirable properties such as high specific stiffness, high specific strength, high coefficient of thermal expansion, increased fatigue resistance and superior dimensional stability compared to unreinforced alloys. In the present work an attempt has been made to develop composites using Al 6061 as a matrix material reinforced with Zircon particulates using stir casting technique. The Zircon particulates were varied in steps of 0 %, 3%, 6%, 9% and 12%. The Specimens were prepared as per the ASTM standards. The prepared composites were characterized by microstructural studies using optical microscope and tensile strength and hardness properties were evaluated. Zircon particles were observed to refine the grains and were distributed homogeneously in the aluminium matrix at 9% of Zircon. The tensile and hardness properties were higher in case of composites when compared to unreinforced Al 6061 matrix. Also increasing addition level of Zircon has resulted in further increase in both tensile strength and hardness values and optimum value was obtained at 9% of Zircon. Â